A case of idiopathic thyroid abscess caused by Escherichia coli - Gurbaj Singh; Radhika Jaiswal; Neha Gulati; Elizabeth Campbell Granieri (Greater Baltimore Medical Center, 2019)
Suppurative thyroiditis with an abscess is a rare form of thyroiditis that can present as a diagnostic challenge. Its rarity is attributed to unique features of the thyroid gland that make it resistant to infection. Delay in diagnosis often can lead to morbid complications from the progression of the infection. Although more likely to be caused by gram-positive bacteria, gram-negative organisms are also known to cause this infection which often requires surgical treatment. The authors present a case of thyroid abscess from Escherichia coli from an unknown source.